2002
DOI: 10.1097/00024382-200212000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Does Upregulation of Inducible Nitric Oxide Synthase Play a Role in Hepatic Injury?

Abstract: Lipopolysaccharide (LPS) and gut ischemia/reperfusion (I/R) injury cause reversible liver injury. Because nitric oxide (NO) can have both beneficial and deleterious effects in the gastrointestinal tract, and because the role of NO in gut I/R-induced hepatic injury is unknown, this study examined its role in LPS and gut I/R-induced hepatic injury in the rat. Both LPS and gut I/R caused a similar increase in serum hepatocellular enzymes. LPS but not gut I/R caused a significant increase in upregulation of hepati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
17
0
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 24 publications
7
17
0
1
Order By: Relevance
“…Inducible nitric oxide synthase is a key mediator of tissue injury in both the LPS infusion and hindpaw injection models of inflammation. 32,33 Thus, our demonstration that bilirubin treatment is associated with a significant decrease in nitrate production in response to endotoxin suggests a potential mechanism whereby bilirubin exerts a cytoprotective effect. An inverse association between HO-1 and iNOS has previously been described, such that NO levels decline in the face of increasing HO-1 activity.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Inducible nitric oxide synthase is a key mediator of tissue injury in both the LPS infusion and hindpaw injection models of inflammation. 32,33 Thus, our demonstration that bilirubin treatment is associated with a significant decrease in nitrate production in response to endotoxin suggests a potential mechanism whereby bilirubin exerts a cytoprotective effect. An inverse association between HO-1 and iNOS has previously been described, such that NO levels decline in the face of increasing HO-1 activity.…”
Section: Discussionmentioning
confidence: 82%
“…The cytoplasmic fraction was isolated through centrifugation and the pellet was processed further to obtain nuclear protein, which was quantified using the BioRad assay (Biorad Laboratories, Hercules, CA). Nuclear extracts (6 g protein) were incubated at 25°C in 125 mmol/L hydroxyethylpiperazine-N-2 ethanesulfonic acid (pH 7.9), 2.5 mmol/L ethylenediaminetetraacetic acid, 2.5 mmol/L dithiothreitol, 1% Non-idet-P40, 25% glycerol, 250 mmol/L NaCl, and 1 g dIdC containing 32 Plabeled double-stranded oligonucleotide sequence for the nuclear factor B (NF-B) binding site (5Ј-AGTT-GAGGGGACTTTCCCAGGC-3Ј).…”
Section: Methodsmentioning
confidence: 99%
“…Several isoforms of NOS have been identified and classified as either constitutive enzymes (nNOS and eNOS) dependent on Ca 2+ and calmodulin or inducible (iNOS) independent of Ca 2+ and calmodulin. Inducible NOS (iNOS) is expressed by hepatocytes, and is known to play an important role in a number of pathological conditions including liver injury and disease [3][4][5]. However, it is unclear what role hepatic iNOS plays in the diabetic state.…”
Section: Introductionmentioning
confidence: 99%
“…This variability in the results may be due to differences in the parameters measured, the experimental models employed, and, most important, the selectivity of NOS inhibitors used (19,32). Studies have shown that N G -nitro-L-arginine methyl ester (L-NAME), a nonspecific NOS inhibitor, increases hepatic and intestinal injury following ischemia-reperfusion (I/R) (24,31). A clinical study was recently discontinued because treatment with N G -monomethyl-L-arginine showed higher mortality (25).…”
mentioning
confidence: 99%